(untitled) (Comprehensive Journal of Science, 2025)
Helicobacter pylori is one of the most common chronic bacterial infections globally, causing a wide range of illnesses including gastritis, peptic ulcers, gastric carcinoma, and mucosa-associated lymphoid tissue (MALT) lymphoma